The Relationship Between Patient Satisfaction Levels and Patient Visit Interest at the Lower Paniki Health Center Based on BPJS Scoring - Chensie S. Angkasa; Afif Yuda Kusuma; Felicia Hananto; Oriza Varera; Innocentius Bernarto (Jurnal Indonesia Sosial Teknologi, 2025)
Assessing the quality of services at health centers is an important part because it can indirectly have an impact on improving the degree of public health. Measuring and monitoring the quality of health services is impossible without indicators. Based on the Indonesian Minister of Health Regulation No. 30 of 2022, one of the indicators used to assess the quality of health services is patient satisfaction. The interest of patients to return to the Health Center can be influenced by their experience on previous visits. Patients who are quite satisfied with the health services provided will tend to return to the health center because they feel comfortable and believe in the quality of the services provided. Therefore, this study aims to evaluate the quality of health services based on the component of patient satisfaction at the Paniki Bawah Health Center. Data collection was carried out using a Google Form questionnaire for 100 patients who met the inclusion and exclusion criteria. Statistical analysis was carried out with SmartPLS software. Hypothesis testing is used to analyze the relationship between related variables as shown in the research model. The results showed a strong positive correlation between various dimensions of service quality and overall patient satisfaction. Thus, it can be concluded that the quality of health services at the Paniki Bawah Health Center is highly rated by BPJS patients. Interest in patient visits is also very high, showing satisfaction with the service.